Efficiency of medical technology in measuring service quality in the Nigerian healthcare sector - Taofeeq D., Moshood; Shahryar, Sorooshian; Gusman, Nawanir; Saktioto, Okfalisa (Elsevier Ltd, 2022)
The medical sector is one of the service sectors whose core value is based on quality services. However, maintaining quality within healthcare settings is a complicated task. Medical innovations and quality care are critical in the current market environment, thus creating a strong rivalry between service providers. For this reason, healthcare centers must evaluate the standard of their care. The article examines medical technologies and the quality of the services to see if medical technology will increase the quality of services in the healthcare system in a sustainable healthcare system. This paper followed a systemic literature review using ATLAS.ti 9 tools, in which the proof was saved, classified, and interpreted. Study findings have shown the importance of medical technology in the contemporary era. Further studies found that cleanliness, sanitation, physicians’ expertise, nurses’ abilities, and other aspects, which can be viewed as standard care, impressed patients in the hospital environment. In general, the study results may enable hospital managers and medical staff to perceive medical technology as an essential factor that significantly determines the quality of service in Nigeria's healthcare sector.